Thermal Elastic Mechanics Problems of Concrete Rectangular Thin Plate - Cheng, Xuansheng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book discusses the thermal-elastic mechanics problems of concrete rectangular thin plate. Using theoretical derivation combined with numerical examples, it explains in detail the analytical solution of the deflection, bending moment, thermal vibration and thermal buckling of concrete rectangular thin plate. To facilitate application, the book also includes deflection and bending moment calculation tables of concrete rectangular thin plate with four edges supported and with free boundary conditions.
Introduction -- Thermal bending of concrete rectangular thin plate with four edges supported -- Thermal bending of concrete rectangular thin plate with free boundary -- Thermal buckling of the concrete rectangular thin plate with free boundary -- Thermal vibration of concrete rectangular liquid storage structures.
Keywords: Mechanics, Applied; Solids; Thermodynamics; Multibody systems; Vibration; Mechanics; Civil engineering; Solid Mechanics; Thermodynamics; Multibody Systems and Mechanical Vibrations; Classical Mechanics; Civil Engineering